2002
DOI: 10.2307/3088405
|View full text |Cite
|
Sign up to set email alerts
|

The New Political Economy of Taxation in Advanced Capitalist Democracies

Abstract: We articulate and test an explanation for the remarkable change and continuity in contemporary tax policy in capitalist democracies. We argue that internationalization, domestic eco- T he globalization theory of taxation suggests that the ability of mo bile asset holders to exit national jurisdictions forces policy makers to compete for investment (Tanzi 1995). In the strongest versions of the theory, taxes on capital and other mobile asset holders such as professionals are progressively reduced to the "lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
236
2
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(261 citation statements)
references
References 34 publications
12
236
2
11
Order By: Relevance
“…26 A general problem in this debate is that a high share of wealthy people can be both a cause and a consequence of tax reforms, especially in Switzerland, where voters can influence tax decisions with direct democratic rights. See Schmidheiny 2005. 27 Hallerberg and Basinger 1998;Swank and Steinmo 2002;Hays 2003;Basinger and Hallerberg 2004;Swank 2006;Plümper, Troeger, and Winner 2009;Cao 2010. 28 Radaelli and Kraemer 2008;Genschel, Kemmerling, and Seils 2011;Genschel and Schwarz 2011. 29 Braun and Gilardi 2006;Simmons, Dobbin, and Garrett 2006;Dobbin, Simmons, and Garrett 2007;Gilardi 2012.…”
Section: How Socialization May Attenuate Competitionmentioning
confidence: 99%
“…26 A general problem in this debate is that a high share of wealthy people can be both a cause and a consequence of tax reforms, especially in Switzerland, where voters can influence tax decisions with direct democratic rights. See Schmidheiny 2005. 27 Hallerberg and Basinger 1998;Swank and Steinmo 2002;Hays 2003;Basinger and Hallerberg 2004;Swank 2006;Plümper, Troeger, and Winner 2009;Cao 2010. 28 Radaelli and Kraemer 2008;Genschel, Kemmerling, and Seils 2011;Genschel and Schwarz 2011. 29 Braun and Gilardi 2006;Simmons, Dobbin, and Garrett 2006;Dobbin, Simmons, and Garrett 2007;Gilardi 2012.…”
Section: How Socialization May Attenuate Competitionmentioning
confidence: 99%
“…2 A consequence of this process is that political parties have lost most of their influence on tax policies. Indeed, numerous recent studies have shown that party ideology has no significant influence on the progressiveness of tax systems (Volkerink and De Haan 1999, Galli 2002, Swank and Steinmo 2002, Cusack and Baramendi 2006. Instead, it has been argued that, nowadays, parties pursue welfare redistribution mainly through putting emphasis on distinguished spending policies that favour more than proportionally low income earners such as health care, unemployment, and social spending in general and not through changes in the tax structure.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it suggests that governments use corporate tax cuts as a device to reduce unemployment by attracting new firms (Haufler and 24 Comparing the absolute magnitude of this 6.98% difference with other findings in the literature is not straightforward since studies addressing how trade integration affects tax competition and corporate income tax rates do not generally differentiate between its effect on large and small countries (e.g. Swank and Steinmo, 2002;Winner, 2005;Devereux et al, 2008;Rincke and Overesch, 2011). Genschel and Schwartz (2011, 356) provide the only partial exception.…”
Section: ---Figure 2 About Here ---mentioning
confidence: 93%